2016
DOI: 10.1038/srep38904
|View full text |Cite
|
Sign up to set email alerts
|

Passive exposure to speech sounds induces long-term memory representations in the auditory cortex of adult rats

Abstract: Experience-induced changes in the functioning of the auditory cortex are prominent in early life, especially during a critical period. Although auditory perceptual learning takes place automatically during this critical period, it is thought to require active training in later life. Previous studies demonstrated rapid changes in single-cell responses of anesthetized adult animals while exposed to sounds presented in a statistical learning paradigm. However, whether passive exposure to sounds can form long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…This fact suggests that the MMN-like potential with a deviant-specific characteristic cannot be recorded at least from the surface of the PAC, regardless of the polarity of ERP components, at least, in the present experimental condition. Although previous studies on human being have indicated that the locus of the MMN generator should primarily be in the AC 21,5360 , we failed to detect the MMN-like potential in the present study in which an electrode was placed on the surface of rat PAC. Alternatively there is a report that the MMN-like potential could not be measured epidurally over the dorsal portion of PAC 38 .…”
Section: Discussioncontrasting
confidence: 83%
“…This fact suggests that the MMN-like potential with a deviant-specific characteristic cannot be recorded at least from the surface of the PAC, regardless of the polarity of ERP components, at least, in the present experimental condition. Although previous studies on human being have indicated that the locus of the MMN generator should primarily be in the AC 21,5360 , we failed to detect the MMN-like potential in the present study in which an electrode was placed on the surface of rat PAC. Alternatively there is a report that the MMN-like potential could not be measured epidurally over the dorsal portion of PAC 38 .…”
Section: Discussioncontrasting
confidence: 83%
“…Key questions on statistical learning still remain, such as the how these processes are differentially engaged in the developing and mature brain, as well as the extent to which different brain regions, microcircuits, or single neurons might be involved in domain-general or language-specific tasks. The use of speech sounds with non-human animals, such as non-human primates and rodents, provides insight into the general capacities for statistical learning across species for more direct comparisons with human studies (Newport et al 2004;Toro and Trobalón 2005;Pons 2006;Saffran et al 2008;Wilson et al 2013;Attaheri et al 2015;Wilson et al 2015;Wilson et al 2015b;Kurkela et al 2016;Milne et al 2016). Moving forward, studying the role of statistical learning with particular relevance to each species' vocal repertoire and ecological significance may ultimately provide better insight into the neural correlates of these processes (Santolin & Saffran 2018).…”
Section: Resultsmentioning
confidence: 99%
“…While there is an extensive literature on stimulus-specific adaptation (Ruusuvirta et al 1998;Nelken & Ulanovsky 2007;Yaron et al 2012;Nelken 2014) and the representation of stimulus statistics in the rodent auditory cortex (Zhang et al 2001;de Villers-Sidani 2007;Insanally et al 2009;Köver et al 2013), combined behavioral and neurobiological studies on statistical learning of vocalizations have been fewer in number. Furthermore, relevant studies in rodents have utilized human syllables as the stimulus set (Toro and Trobalón 2005;Pons 2006;Kurkela et al 2016), which gives us insight into general learning capacities but with limited ethological relevance.…”
Section: Capacities For Statistical Learning and Rodent Vocalizationsmentioning
confidence: 99%
“…However, the MMN amplitude did not show any changes due to the passive exposure, although it typically increases in studies utilizing active training (Näätänen et al, 1993;Kraus et al, 1995;Tremblay et al, 1997). Also in our previous study in rats, 36-h passive exposure to spectro-temporal changes in speech sound /a/ enhanced the mismatch response amplitude (Kurkela et al, 2016).…”
Section: Discussionmentioning
confidence: 48%